Infectious Triggers in Periodontitis and the Gut in Rheumatoid Arthritis (RA): A Complex Story About Association and Causality - Möller, Burkhard; Kollert, Florian; Sculean, Anton; Villiger, Peter M. (Frontiers in Immunology, 2020)
Rheumatoid arthritis (RA) is a systemic immune mediated inflammatory disease of unknown origin, which is predominantly affecting the joints. Antibodies against citrullinated peptides are a rather specific immunological hallmark of this heterogeneous entity. Furthermore, certain sequences of the third hypervariable region of human leukocyte antigen (HLA)-DR class II major histocompatibility (MHC) molecules, the so called ‘shared epitope’ sequences, appear to promote autoantibody positive types of RA. However, MHC-II molecule and other genetic associations with RA could not be linked to immune responses against specific citrullinated peptides, nor do genetic factors fully explain the origin of RA. Consequently, non-genetic factors must play an important role in the complex interaction of endogenous and exogenous disease factors. Tobacco smoking was the first environmental factor that was associated with onset and severity of RA. Notably, smoking is also an established risk factor for oral diseases. Furthermore, smoking is associated with extra-articular RA manifestations such as interstitial lung disease in anatomical proximity to the airway mucosa, but also with subcutaneous rheumatoid nodules. In the mouth, Porphyromonas gingivalis is a periodontal pathogen with unique citrullinating capacity of foreign microbial antigens as well as candidate RA autoantigens. Although the original hypothesis that this single pathogen is causative for RA remained unproven, epidemiological as well as experimental evidence linking periodontitis (PD) with RA is rapidly accumulating. Other periopathogens such as Aggregatibacter actinomycetemcomitans and Prevotella intermedia were also proposed to play a specific immunodominant role in context of RA. However, demonstration of T cell reactivity against citrullinated, MHC-II presented autoantigens from RA synovium coinciding with immunity against Prevotella copri, a gut microbe attracted attention to another mucosal site, the intestine. Prevotella copri was accumulated in the feces of clinically healthy subjects with citrulline directed immune responses and was correlated with RA onset. In conclusion, we retrieved more than one line of evidence for mucosal sites and different microbial taxa to be potentially involved in the development of RA. This review gives an overview of infectious agents and mucosal pathologies, and discusses the current evidence for causality between different exogenous or mucosal factors and systemic inflammation in RA.